2013
DOI: 10.3389/fnhum.2013.00546
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Lateralization Interrupted: Material-Specific Memory Deficits in Temporal Lobe Epilepsy

Abstract: The hemispheric lateralization of memory has largely been informed through the study of patients with temporal lobe epilepsy originating from medial temporal sources (mTLE). The material-specific model of memory relies on the basic framework that the left temporal lobe mediates verbal memories, while the right temporal lobe mediates non-verbal memories. Over the years, this model has been refined, and even challenged, as our understanding of the material-specific memory deficits in mTLE has been further elabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 127 publications
(185 reference statements)
4
25
0
1
Order By: Relevance
“…Interestingly, using multivoxel pattern analysis, one previous study found that the activity patterns of specific memories were detected in a contralateral HIP, but not a sclerotic HIP, in patients with TLE. 26 Similarly, the present study demonstrated that activations in the contralateral, but not the ipsilateral, HIP were correlated with the memory performance of MTLR patients. It seems that the ipsilateral posterior HIP is more strongly related to other clinical variables, including the duration of illness and age at seizure onset, rather than individual memory capacity.…”
Section: Activations In Hippocampus Ipsilateral To Resection Sidesupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, using multivoxel pattern analysis, one previous study found that the activity patterns of specific memories were detected in a contralateral HIP, but not a sclerotic HIP, in patients with TLE. 26 Similarly, the present study demonstrated that activations in the contralateral, but not the ipsilateral, HIP were correlated with the memory performance of MTLR patients. It seems that the ipsilateral posterior HIP is more strongly related to other clinical variables, including the duration of illness and age at seizure onset, rather than individual memory capacity.…”
Section: Activations In Hippocampus Ipsilateral To Resection Sidesupporting
confidence: 75%
“…According to the material-specific memory model, verbal memory is generally more dependent on the left (dominant hemisphere) medial temporal lobe (MTL) structures while visual memory is more dependent on the right MTL structures. 26 However, in the present study, the contralateral right HIP performed the role of verbal memory function of the left HIP in patients who underwent left HIP resection. In contrast, the contralateral left HIP performed the role of the visual memory function of the right HIP in patients who underwent right HIP resection.…”
Section: Activations In Hippocampus Contralateral To Resection Sidementioning
confidence: 54%
“…Therefore, we hypothesized that hippocampal subfield volumes that were smaller in PBTS compared with TDC would correlate with episodic memory performance. Although verbal memory lateralization is not present in all individuals (Catani et al, ), lesion studies in adults (Saling et al, ) and children with epilepsy (Gleissner et al, ; Leunen et al, ) suggest that the left hemisphere plays a particularly important role in verbal memory in most individuals (for a review, see Saling, ; Willment & Golby, ). Based on this research, we expected that the left hippocampal subfields would have stronger associations with verbal memory in PBTS than the right subfields.…”
Section: Introductionmentioning
confidence: 99%
“…In up to 80% of TLE, epilepsy surgery can be curative (4), however, cognitive decline remains a significant complication of epilepsy surgery (5)(6)(7)(8)(9)(10). Early onset seizures interfere with the normal process of hemispheric lateralization (11) and may result in the reorganization of memory functions (12)(13)(14). In unilateral TLE, both the function of the contra-lateral MTL (hippocampal adequacy theory), and functional reserve of the ipsilateral hippocampus have been posited in the maintenance of post-operative memory functions (15).…”
Section: Introductionmentioning
confidence: 99%